MANEJEMEN KOMUNIKASI PT. P&P BANGKINANG DALAM MENANGANI KELUHAN MASYARAKAT TERKAIT LIMBAH INDUSTRI - Permatasari, Minda; Rasyid, Anuar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
PT. The P & P Bangkinang is engaged in the rubber industry. The company's activities will produce products and waste, the product will be profitable for the company but waste can be detrimental to the surrounding community. Waste produced by PT. The Bang Pang P & P is solid, liquid (polluting the river ecosystem) and air pollution. The community is very disturbed by the company's operations because it produces a stinging rubber odor. Thus the research conducted aims to determine how communication management is carried out by PT. P & P Bangkinang in Handling Community Complaints Regarding Industrial Waste.This study used qualitative research methods. The subject of this study consisted of Management Representatives of PT. Bangkinang P & P 1 informant and 2 representatives from the community living around PT. The Bangkinang P & P was chosen by using Purposive Sampling techniques, data collection was used through interviews, documentation, and observation. And for checking the validity of the data the authors took part in and also tringulated. The results of the study show that (1) the planning of PT. The Bangkinang P & P for handling community complaints through internal company discussions, where the company establishes an approach process must be a priority in response to community complaints. (2) the implementation of complaints handling provided by the community on the operations of the PT. P & P Bangkinang Company, the direction of the process goes from top to bottom, namely the leader gives instructions to the Public Relations to negotiate community complaints regarding industrial waste. Keywords: Communication Management, Public Complaints